Modulation of the inflammatory response to decellularized collagen matrix for cartilage regeneration - Gvaramia, David; Kern, Johann; Jakob, Yvonne; Tritschler, Hanna; Brenner, Rolf E.; Breiter, Roman; Kzhyshkowska, Julia; Rotter, Nicole (Journal of biomedical materials research, 2022)
Journal of Biomedical Materials Research Part A is a biomaterials journal at the interface of materials science & biomedicine, covering medicine, biology & engineering.
"First published: 29 December 2021".- Artikelhomepage
Gesehen am 21.09.2023